Ответ:
Пошаговое объяснение:
х² - 15х - 16 = 0
а = 1; b = -15; c = -16
D = b² - 4ac
D = (-15)² - 4*1*(-16) = 225 + 64 = 289
D > 0, значит уравнение имеет 2 корня
х1 = (-b-√D)/2a
x1 = (15 - √289)/(2*1) =
(15-17)/2 = -2/2 = -1
x2 = (-b+√D)/2a
x2 = (15 + √289)/(2*1) =
(15+17)/2 = 32/2 = 16
Ответ: -1; 16.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
х² - 15х - 16 = 0
а = 1; b = -15; c = -16
D = b² - 4ac
D = (-15)² - 4*1*(-16) = 225 + 64 = 289
D > 0, значит уравнение имеет 2 корня
х1 = (-b-√D)/2a
x1 = (15 - √289)/(2*1) =
(15-17)/2 = -2/2 = -1
x2 = (-b+√D)/2a
x2 = (15 + √289)/(2*1) =
(15+17)/2 = 32/2 = 16
Ответ: -1; 16.